Hubungan antara work-family enrichment dengan work engagement pada perawat wanita - Kuntari, C. M. Indah Soca R. (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2015)
A young, married nurse has to play dual roles in her life: in a work and family setting. Playing dual roles does not always end in a conflict, but can also enrich one’s experience and increase one’s quality of life. Work-family enrichment occurs when experience in the work situation enriches the role in family context, and vice versa. The increasing of quality of life can boost up courage and positive psychological experience when playing a role as a professional nurse, which may result in the increased work engagement. The aim of this study is to explore the relationship of work-family enrichment and work engagement of the female nurse. Participants in this study were 53 married, female nurses. Instruments used in this study were Work-Family Enrichment Questionnaire and Utrech Work Engagement Questionnaire. The result showed the existence of positive correlation between work-family enrichment and work engagement. It is concluded that the increased work-family enrichment can also result in the increased work engagement.